A Macroeconomist’s View on EU Governance Reform: Why and How to Establish Policy Coordination? - Gabrisch, Hubert (Economic Annals, 2011)
This paper discusses the need for macroeconomic policy coordination in the E(M)U. Coordination of national policies with cross-border effects does not exist at the macroeconomic level, although requested by the EU Treaty. The need for coordination stems from current account imbalances, which origin in market-induced capital flows, destabilizing the real exchange rates between low and high wage countries. The recent attempts of the Commission and the European Council to reform E(M)U governance do not address this problem and thus remain incapable to protect against future instability. Macroeconomic coordination needs (i) a clear identification of union-wide employment goals, and (ii) the establishment of a high level institution responsible for coordination following these objectives. The paper proposes a High Representative for Economic Policy, equipped with an appropriate office and supported by a Council of Economic Advisers committed to the union-wide objectives.